Common Lexical Errors Made by Machine Translation On Cultural Text - NANDA FITRI MAR'ATHUS SHOLIKHAH; Rohmani Nur Indah (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Machine translation is one tool of Google that presents various languages to translate. As a translator machine, the results of Google Translate are not always perfectly correct. The result of translation can be called pre-translation, which is still needed to be revised. Pramoedya Ananta Toer's Arok Dedes story is one of the Javanese stories that contain elements of culture. Translating texts which contain elements of a culture is not easy because one region to another have different cultures, so that it is difficult to look for parallel words that contain cultural, religious, social, customs, social organization, procedure, sign language, and ecology elements, and Google cannot translate the term of cultural words easily. This study is aimed at two main purposes: (1) finding out the types of lexical errors made by machine translation in translating cultural text and (2) knowing the most dominant type of lexical errors made by machine translation in translating cultural text. This study was carried out in a population of 553 pages of Pramoedya Ananta Toer's Arok Dedes. A simple random sampling technique was done to select samples. The total samples taken in this study were 30% of the population. The study results are that there are only 9 types of the total 21 types of lexical errors, namely calque, misselection, consonant-based type, false friend, vowel-based type, inappropriate co-hyponym statistically weighted preferences, semantically determined word selection, and preposition partners. The most dominant error of lexical errors is calque.